2021
DOI: 10.32598/cmja.11.3.1067.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Protocol of Warm and Cold Uterine Temperaments Based on Persian Medicine: A Qualitative Study

Abstract: Objective: Uterus is an important body organ in women responsible for purifying blood and carrying fetus. In Traditional Iranian Medicine (TIM), identifying the uterine temperament (mizaj) is necessary for prevention, diagnosis and treatment of this organ’s diseases. Many gynecological disorders in TIM including infertility, oligomenorrhea, amenorrhea, hypermenorrhea, vaginitis, cervicitis, urinary incontinence and pelvic pain are related to uterine distemperament (Su-e mizaj). Therefore, their appropriate tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In recent studies, the most common temperament found in patients with infertility complaints was cold and wet. It was also confirmed that the temperament of the uterus is related to the hot/cold temperament of the body and pelvic width (14,15). Folk remedy emphasizes the hot (harr) property of U. pilulifera, suggesting that it can potentially increase the quantity of semen and enhance sexual libido and arousal in both males and females.…”
Section: Diminished Ovarian Reserve (Dor) Is Used Tomentioning
confidence: 71%
“…In recent studies, the most common temperament found in patients with infertility complaints was cold and wet. It was also confirmed that the temperament of the uterus is related to the hot/cold temperament of the body and pelvic width (14,15). Folk remedy emphasizes the hot (harr) property of U. pilulifera, suggesting that it can potentially increase the quantity of semen and enhance sexual libido and arousal in both males and females.…”
Section: Diminished Ovarian Reserve (Dor) Is Used Tomentioning
confidence: 71%
“…Warm-wet uterine dystemperament prevalence was the highest (78.78%-74.74%) in AVD participants. Dystemperament of the uterus holds significant importance in uterine diseases; hence diagnosis and treatment depend upon the determination of individual and organ temperament [4]. A study found dry dystemperament of the uterus in all menopausal transition participants [17].…”
Section: General Temperament Abnormal Vaginal Discharge Andmentioning
confidence: 99%
“…An individual's temperament is maintained and preserved by humour (Akhlat) [2]. ere are four types of temperaments, namely, warm, cold, wet, and dry, in Unani medicine [4], and they are related to four humours, namely, sanguine, phlegmatic, choleric, and melancholic [1,2]. Each organ also has its specific temperament in addition to general body temperament [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with cold-wet Mizaj or the related coldwet dystemperament are prone to diseases such as joint pain and inflammation, headaches, sinusitis, infectious and febrile diseases, lung disorders, digestive disorders and weakness, weight gain (leading to conditions like cardiovascular disorders, fatty liver, and diabetes), dysmenorrhea, infertility, and mental disorders (30,(33)(34)(35)(36)(37)(38)(39)(40)(41). Moreover, many symptoms of this dystemperament are consistent with conditions of unknown etiology in conventional medicine, including weakness and fatigue.…”
Section: Introductionmentioning
confidence: 99%